Sacrificing power for more cost-effective treatment: A techno-economic approach for engineering microbial fuel cells. (October 2016) - Stoll, Zachary A.; Ma, Zhaokun; Trivedi, Christopher B.; Spear, John R.; Xu, Pei
Abstract: Microbial fuel cells (MFCs) are a promising energy-positive wastewater treatment technology, however, the system's cost-effectiveness has been overlooked. In this study, two new anode materials – hard felt (HF) and carbon foam (CF) – were evaluated against the standard graphite brush (GB) to determine if using inexpensive materials with less than ideal properties can achieve more cost-effective treatment than high-cost, high-performing materials. Using domestic wastewater as the substrate, power densities for the GB, HF and CF-MFCs were 393, 339 and 291 mW m −2 normalized by cathodic surface area, respectively. Higher power densities correlated with larger anodic surface areas and anodic current densities but not with electrical conductivity. Cyclic voltammetry revealed that redox systems used for extracellular electron transport in the GB, HF and CF-MFCs were similar (−0.143 ± 0.046, −0.158 ± 0.004 and −0.100 ± 0.014 V vs. Ag/AgCl) and that the electrochemical kinetics of the MFCs showed no correlation with their respective electrical conductivity. 16S rRNA sequencing showed the GB, HF and CF microbial community compositions were not statistically different while organic removal rates were nearly identical for all MFCs. The HF-MFC generated a power output to electrode cost (W −1 ) 1.9 times greater than the GB-MFC, despite producing 14% less power and 15% less anodic current, while having 2.6 times less anodic surface area, 2.1 times larger charge transfer resistance and an electrical conductivity three orders of magnitude lower. The results demonstrate that inexpensive materials are capable of achieving more cost-effective treatment than high-performing materials despite generating lower power when treating real wastewater. Graphical abstract: Highlights: Power density correlated with the anode specific surface area. Power density did not correlate with anode conductivity or internal resistance. No statistical difference between MFCs' electrochemical or biological properties. Inexpensive anode materials are cost-effective despite having non-ideal properties.